Executive Committees Of Local Sections (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1923)
New York Holds monthly meetings, except June, July and August J E SPURR, Chairman A D BROKAW, Vice-chairman SIDNEY ROLLE, Vice-chairman M H MERRISS, Secretary-treasures, Nichols Copper Co, 25 Broad St, New York M F CHASE KARL HOFFMAN Boston Meets first Monday of each winter month C R HAYWARD, Chairman E C GEITHER, Vice-chairman D H McLAUGHLIN, Secretary-treasurer, Rotch Bldg, Harvard Univ Cambridge, Mass GEO H GILMAN GEO A PACKARD